(3GdMOGFb GdhQOjI aj efGbH GdCFeI GdRjOjIs - (3MejO Hf CMeO GdnenMpqdj GdgeOGfqj, CHh YHO Gddg MSGe GdOjf, GdeYQha HGdbGVj GdTgjO,J (B652 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CaGV YdjfG CfhGQ GdgOGjI CeG HYO , aEf Chdi ef CSYa eQGOg , ef UaG ai GdOjf EYJbGOg bO HdZfG cJGH GdbGVi GdCLd efWhjkG Ydi GdSDGd Yf JcJ TGajI ef CNHGQ GdSGHbjf s
(3BNQgG (B:s
(3ef bUjOI GdgjKe Hf YHO Gddg GdNKYei , jQKi CHG GdSQGjG , bhdg (B: (3gdG hbGd GdQOi GdLHGf EPG VGbJ Ydjg HfaSg GdMjd hGdehJ eHShWI MHGFdg hGdfGS fGL efge heNJHd Je GdLRA GdChd ef GdMOGFb GdhQOjI , HMeO Gddg s
(3UhQJ Yf fSNI ehLhOg HGdLGeY GdcHjQ HUfYGAs
(3ai JQGLe CFeI GdRjOjIs
(3ai GdeYgO fSNJGf CNQjGf HQbe (B212 (3JGQjN hPcQfG GdYfhGf GdeKHJ Ydi GdfSNI hai fSN CNQi JZjjQ Wajas
(3cJHJ Hbde eged GdfbW CMjGfkG HgG WeS s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B282 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B83s
Keywords: (3GdJGQjNs